Localization of angiotensin II (AT1)-receptor-immunoreactive fibres in the hypothalamus of rats: angiotensin II-sensitive tanycytes in the ependyma of the third ventricle? - Thomas, Martin Alexander; Hauptfleisch, Stefan; Fleissner, Gerta; Lemmer, Björn (Brain research, 2003)
Scanning the hypothalamus of rats for receptor binding sites of the octapeptide hormone angiotensin II (ANG II), we observed ANG II-sensitive fibres in the ventrolateral hypothalamus. The ANG II (AT1)-receptor-immunoreactive processes originate from cells - probably tanycytes - embedded in the base and the ventrolateral walls of the third ventricle and reach into the retrochiasmatic area, the ventrolateral hypothalamus and the median eminence.
Gesehen am 28.03.2022
Im Titel ist die Ziffer 1 tiefgestellt